Phytochemicals in food industry by-products: the case of coffee silverskin - Costa, A. (2021)
Recovery of waste and added value by-products in the food industry is mandatory in a society that aims environmental, social and economic sustainability. It promotes waste reduction and gains instead of expenses. In the present study, we used coffee silverskin, a by-product (with no added value) of coffee roast industry, as a possible source of phytochemicals with antioxidant activity. Silverskin from three commercial coffee batches (a pure robusta and two blends with arabica and robusta coffees) were provided by a local coffee torrefaction industry.